Microwave energy supplied by a prototype oven prevents the spread of Fusarium wilt during the propagation of melon plantlets by seed - Soriano-Martín, M. L.; Porras-Piedra, A.; Marcilla Goldaracena, I.; Porras-Soriano, A.; Martín-Sánchez, D.; León-Egido, M.; Porras-Soriano, M. L.; Porras-Soriano, R. (Spanish Journal of Agricultural Research, 2006)
The re-use of propagation trays in nursery greenhouses is one of the main ways in which fusarium wilt is spread in melon crops (Cucumis melo). The causal agent of the disease is the fungus Fusarium oxysporum f. sp. melonis. This paper reports that exposing these seed trays to the energy produced by a prototype microwave oven during the commercial production of melon plantlets can prevent the spread of this pathogen with only a very small increase in production costs.